Menguatkan Tradisi Keilmuan Islam melalui Pembelajaran Kitab Turats di Madrasah Aliyah - Muqorrobin, M Rizqil Hasan; Nurhamsalim, Mohammad; Muttaqien, Moh Hasan Firghol (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This study examines the implementation of turats book learning as a distinctive program at Madrasah Aliyah Ainul Hasan Wonorejo, Maron District, Probolinggo Regency. The background of this research is the continuity of classical Islamic learning traditions amid the modernization of madrasah education. This study aims to describe the implementation, historical background, and learning methods of turats book instruction. The research employs a qualitative approach using data collection techniques such as interviews, observation, and documentation. The main informant in this study is the principal of Madrasah Aliyah Ainul Hasan. The findings indicate that turats book learning has been consistently implemented since 2010 based on the initiative of the late KH. Ahsan Bahrul Ulum, Chairman of the Ainul Hasan Mandiri Foundation. The learning activities are conducted every morning before formal classroom instruction, from 07.00 to 08.00 a.m., using the books Uqud al-Lijain and Fathul Qarib. The learning method resembles the sorogan method, in which the teacher reads and explains the text while students listen and annotate its meaning. This program has become a distinctive characteristic of the madrasah and contributes to strengthening students’ religious understanding and Islamic character.